SYSTEMATIC LITERATURE REVIEW: PENGARUH ISU-ISU SOSIOSAINTIFIK TERHADAP KEBERHASILAN PELAJARAN KIMIA DI SEKOLAH MENENGAH ATAS - Kansha, Tsabitah; Miterianifa, Miterianifa; Aulia, Lisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research explores the impact approaching socioscientific issues on student learning succes in secondary school chemistry. The study utilizied a Systematic Literature Review (SLR) examining eight articles published beetwen 2020 and 2024 that met specific isssues in chemistry education. Steps of a Systematic Literature Review (SLR), 1) Google scholar (n=1000), 2) Searching results (n=35), 3) Reamining (n=32), 4) Screening of remaining (n=25), 5) Eligible articles (n-8). The findings show that this approach improves students understanding of key chemistry topic, especially acid-base chemistry, petroleum, and hidrocarbons. The laerning models applied in this study include Problem Based Learning (PBL) and discovery learning, both of wich effectively increase student engagement. The data showed the student in the experimental class applying the socio scientific approach achieved and average score of 65.16, compared to an average score of 50.87 in the control class. Relevan issues to discuss in the educational context include the environmental impact of chemical use, dependence on fossil fuels, and chemical waste management. Overall, this study has important implication for curriculum development and teaching metods in chemistry education, highlighting the importance of intergrating contemporary issues into the teaching and learning process.